pengaruh whistleblowinh system, kompetensi aparatur desa dan sistem pengendalian internal terhadap pencegahan fraud pengelolaan keuangan desa - Purboningsih, Antin Tri (Universitas Slamet Riyadi, 2021)
Fraud prevention is an effort to reduce the factors that cause fraud by minimizing the opportunity for opportunities to commit fraud. This study aims to determine (1) The effect of the whistleblowing system on fraud prevention (2) The effect of village apparatus competence on fraud prevention (3) The effect of the internal control system on fraud prevention in village financial management. This research was conducted on village officials in Sine District, Ngawi Regency, the type of data used is quantitative data. The data source used is primary data. The data collection technique used a questionnaire with a population of sampling using purposive sampling. The population in this study were all parties involved in the preparation of village finances in Sine District, Ngawi Regency. The sample in this study was 60 village officials including the Village Head, Village Secretary, Head of Financial Affairs, and Head of the Village Consultative Body (BPD). The results of this study indicate that the whistleblowing system has a significant effect on the prevention of fraud in village financial management in Sine District, Ngawi Regency. The competence of village officials has a significant effect on the prevention of fraud in village financial management in Sine District, Ngawi Regency. The internal control system has a significant effect on the prevention of fraud in village financial management in Sine District, Ngawi Regency. Keywords: Whistleblowing System, Village Apparatus Competence, Internal Control System and Village Financial Management Fraud Prevention.